Rancang Bangun Sistem Kontrol Semiotomatis Penggulung Barcode Berbasis Mikrokontroler - Muhammad Kahlil Firdausi; Adik Susilo Wardoyo; Diba Aliya Faradilla (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2026)
This study aims to design an automatic barcode rolling device based on an Arduino Uno microcontroller, with a focus on developing the electrical system as the main controller. The system consists of a DC motor as the main drive, a motor driver to control the direction and speed of the motor, a proximity switch as a sensor to detect the end of the paper, and a potentiometer to adjust the rotation speed. The electrical circuit is designed so that the rolling process can operate automatically and stop precisely without operator intervention. Processing time was measured using the time study method before and after the implementation of the device. The results showed that the manual rolling time of 183.7 seconds decreased to 87.2 seconds with the automatic device. The paired sample t-test produced a p-value of 0.000 (p < 0.05), indicating a significant improvement. The achieved time efficiency of 52.5% proves that the designed electrical system significantly enhances the device’s performance.